The Influence of the PBL Model Accompanied by Canva Al Animation Videos on Critical Thinking Skills in Elementary School Science Learning - Gita Indah Pratiwi; Singgih Bektiarso; Trapsilo Prihandono (Journal of Pedagogi, 2025)
In the science learning process, one of the abilities that needs to be developed to achieve 21st century skills is the ability to think critically in solving or resolving problems. Critical thinking is an important competency that must be developed through learning. In the science learning process, one of the abilities that needs to be developed to achieve 21st century skills is the ability to think critically in resolving or solving problems. Students' critical thinking abilities must be honed and trained in the classroom. There are lots of learning media that use the latest technology in the era of society 5.0, one of which is animated video learning media. Efforts to develop students' optimal critical thinking skills require interactive classes, students are seen as thinkers, not people being taught, and teachers act as mediators, facilitators and motivators who help students learn, not teach. Animated videos are a different learning media and can make students focus on learning, namely animated video-based learning media. Animation is a collection of images that will be processed in such a way that they can produce movement. This research aims to test the effect of the PBL model accompanied by Canva AI animated videos on critical thinking skills in science learning.  The use of video media in the form of animated video media can provide a good response to students. Data collection methods include interviews, observations, and learning outcomes tests to measure students' critical thinking abilities. The data analysis technique used was a normality test with a t test with an independent sample t test which showed that the PBL model accompanied by Canva AI animation videos had a significant effect on critical thinking skills.